BIOTECHNOLOGY IN COIR EXTRACTION & WASTE UTILIZATION - Anita Das Ravindranath (International Coconut Community, 2001)
Coir, the fibre extracted from the mesocarp of the drupe of the coconut palm cocos nucifera is used for the production of beautiful products like mats, matting, carpet, handicrafts etc. (Table I) Coir suits very well for geotextiles and insulating materials and being environment friendly has an edge over synthetics for application in environmental operations.